HOUSEHOLD HAZARDOUS WASTE PROGRAM: POPULATION DEMOGRAPHICS - Shulse, Taylor (My University, 2016)
My master’s project and field experience provided me with a wide variety of opportunities for personal growth, as well as acquainted me with the different aspects of the field of public health. My capstone project developed a method by which the Johnson county Household Hazardous Waste site was able to consolidate their data in a way to quickly analyze the results from the 92,402 appointments they have developed from the past 12 years and will continue to add data. Principally my project and field experience focused on organization of data and analysis of the areas we serve, and potential demographics or areas of the county the site might not be serving sufficiently. I was able to visualize the data through the use of a geographic information system. This program allows public health workers to visualize, question, analyze, and interpret data to understand relationships, patterns, and trends. This program was essential to understanding what is happening and what might happen in a geographic space. The household hazardous waste site is a county funded facility that is critical to the health and safety of not only the environment by keeping hazardous waste out of the city dumps, but also gives people a place to dispose of their environmentally hazardous chemicals in a safe way. Lastly my project was accepted by the North American Hazardous Materials Management Association (NAHMMA) to be presented, where my preceptor Julie Davis will present the data and PowerPoint I put together for her. In this report, I will discuss the project and field experience
Keywords: Household hazardous waste; Johnson County Kansas